2020
DOI: 10.3389/fpsyt.2020.00707
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of the Frontal Cortical Oscillatory Dynamics Underlying Inhibitory Control During a Go/No-Go Task as a Predictive Biomarker in Major Depression

Abstract: Background Major depressive disorder (MDD) is characterized by core functional deficits in cognitive inhibition, which is crucial for emotion regulation. To assess the response to ruminative and negative mood states, it was hypothesized that MDD patients have prolonged disparities in the oscillatory dynamics of the frontal cortical regions across the life course of the disease. Method A “go/no-go” response inhibition paradigm was tested in 31 MDD patients and 19 age-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 83 publications
(138 reference statements)
0
14
0
Order By: Relevance
“…Using SST, Li et al (2021) found a longer stop‐signal response time (SSRT) to digital characters stimulus in patients with MDD. Similarly, Han et al (2020) also found a longer reaction time and a lower accuracy rate in the no‐go task using pure color picture stimuli in patients with MDD. With respect to inhibition of emotional response, a study found that patients with MDD showed longer stop‐signal reaction time for both negative and positive emotion words than healthy controls (Lau et al, 2007).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Using SST, Li et al (2021) found a longer stop‐signal response time (SSRT) to digital characters stimulus in patients with MDD. Similarly, Han et al (2020) also found a longer reaction time and a lower accuracy rate in the no‐go task using pure color picture stimuli in patients with MDD. With respect to inhibition of emotional response, a study found that patients with MDD showed longer stop‐signal reaction time for both negative and positive emotion words than healthy controls (Lau et al, 2007).…”
Section: Introductionmentioning
confidence: 77%
“…Researchers believe that response inhibition deficit may be one of the endophenotypes of depression (Goldstein & Klein, 2014). Some studies have found evidence of the defect in response inhibition to non‐emotional stimuli in MDD patients (Han et al, 2020; Lau et al, 2007; Li et al, 2021), but others have not (Nixon et al, 2013; Lyche et al, 2010; Westheide et al, 2007). Similar to the latter, we did not find impaired response inhibition to non‐emotional stimuli in individuals with SD.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we chose the Benjamin-Hochberg method for the adjustment of multiple comparisons due to the relatively small sample size in our study. And, we performed post hoc analysis in each frequency band (i.e., 10 comparisons) separately based on the previous studies [32,61] to examine the significance between any two brain regions in different frequency bands. To acquire more valid statistical results, more stringent multiple testing corrections (e.g., Bonferroni correction) should be used in future studies with larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…reported that older age is a risk factor for suicide attempts 43 . The duration of illness is a negative factor for mood disorders, and a longer duration of illness gives them time to develop their illness and accumulate adverse consequences, such as suicide attempts 44,45 . In our study, we found that suicide attempters had severe depressive symptoms and psychotic symptoms.…”
Section: Socio-demographic and Clinical Characteristicsmentioning
confidence: 99%